Implementation of a Project-Based Learning to the coordination of subjects in the Agrifood and Rural Engineering Bachelor - Mª Tatiana Pina Desfilis; Ernestina Aguilar Fenollosa; Gemma Camañes Querol; Ana I. Marqués Marzal; Alma Rodríguez-Sánchez; Emma Fernández-Crespo; Eugenio Llorens Vilarrocha; Loredana Scalschi; María Jesús Máñez Pitarch; Josep Jacas Miret; Begonya Vicedo; Leonor Lapeña (Red U, 2015)
The Bachelor’s Degree in Agrifood and Rural Engineering at Universitat Jaume I of Castelló has implemented in the second academic year a multidisciplinary project using a Project-Based Learning as the teaching method. Its final purpose is the acquisition of skills that should help the students to cope with their future career. This teaching-learning system has been  used  for  three  consecutive  years since the degree was firstly implemented. Once  a  particular  farm  is  assigned,  the students are organized in groups and must   fulfill   their   assigned   tasks   in   a collaborative manner with the final goal of developing a project on that farm including viable improvements of the exploitation,   taking   into   account   the issues  related  to  the  different  subjects involved.  This  work  presents  the  results obtained along the three years, analyzed from two different points of view: student satisfaction    and    learning    outcomes. Besides,  the  proposals  for  improvement of   the   weaknesses   identified   during the process are presented. The results show that the used method has   promoted   the   acquisition   of   the competences proposed. Moreover the multidisciplinary   approach   has   led   to better results in the student performance than those obtained by students enrolled in an unidisciplinary project. Although improvement  actions  have  solved  some of the problems detected, there are still some   weaknesses,   mainly   related   to team  working  and  tutorials  that  should be addressed in the future.